2009
DOI: 10.1007/s00436-009-1502-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy and Safety of Two Treatment Regimens with a Topically Applied Combination of Imidacloprid and Moxidectin (Advocate®) against Generalised Demodicosis in Dogs

Abstract: This laboratory study compared the efficacy of two treatment regimens using an imidacloprid (10%)/moxidectin (2.5%) topical formulation (Advocate, Bayer) on dogs with generalised demodicosis. Sixteen dogs were randomly allocated to two equal groups. One group was treated at 28-day intervals for 12 weeks and the second group at weekly intervals for 15 weeks. Mite numbers were estimated and demodectic lesions were evaluated on each dog before treatment and at approximately 28-day intervals thereafter. Consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
0
19
0
2
Order By: Relevance
“…The spot-on formulation containing 10 per cent imidacloprid and 2.5 per cent moxidectin (Advocate, Bayer; Prinovox, Virbac) is licensed for weekly use in severe cases of demodicosis and for monthly use in collies and related breeds. It has been evaluated in several studies and is recommended for the treatment of CGD due to its efficacy at weekly dosing (Heine and others 2005, Fourie and others 2009, Mueller and others 2009). After topical application it is rapidly distributed over the dog's skin within one day, with the moxidectin peak plasma level seen within four to nine days.…”
Section: Treatmentmentioning
confidence: 99%
“…The spot-on formulation containing 10 per cent imidacloprid and 2.5 per cent moxidectin (Advocate, Bayer; Prinovox, Virbac) is licensed for weekly use in severe cases of demodicosis and for monthly use in collies and related breeds. It has been evaluated in several studies and is recommended for the treatment of CGD due to its efficacy at weekly dosing (Heine and others 2005, Fourie and others 2009, Mueller and others 2009). After topical application it is rapidly distributed over the dog's skin within one day, with the moxidectin peak plasma level seen within four to nine days.…”
Section: Treatmentmentioning
confidence: 99%
“…With the pathogenicity of the mites parasitizing in animals like dog, goat, etc. and human being confirmed successively (Smith 1961;Sheahan and Gaafar 1970;Zhao et al 2010Zhao et al , 2011aZhao et al , b, 2012b, researchers have done some work in the ecology and cultivation of Demodex mites, as well as the therapy of demodicidosis (Heine et al 2005;Xhaxhiu et al 2009;Zhao et al 2009;Fourie et al 2009). It has been reported that the pathogenicity of Demodex is related to population.…”
Section: Discussionmentioning
confidence: 93%
“…Another study (Fourie and others 2009) compared the efficacy of a spot-on formulation containing 10 per cent imidacloprid and 2.5 per cent moxidectin in a monthly application regimen with a weekly regimen. In those studies, a correlation between the success rate and the frequency of application was seen, with weekly application being significantly better than monthly application.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a spot-on formulation containing moxidectin and imidacloprid has been approved as a monthly treatment for demodicosis in Europe. Reported success rates vary in different studies between 39.4 per cent (Mueller and others 2008) and 86.7 per cent (Heine and others 2005), but dogs with mild to moderate disease have been shown to respond better than dogs with severe demodicosis (Mueller and others 2008, Fourie and others 2009), and weekly administration resulted in higher remission rates than monthly administration (Paterson and others 2008). …”
mentioning
confidence: 99%